Perancangan Pembuatan Aplikasi Pengenalan Dan Penerjemah Bahasa Isyarat SIBI Menggunakan Leap Motion dengan Hidden Markov Models - Nimatul Mamuriyah; Deasy Deasy (Universitas Internasional Batam, 2020)
ABSTRACT Sign language is a form of communication used by persons with disabilities who are deaf to communicate through movement. Every movement in sign language has a meaning that not everyone can understand. To be able to translate the meaning of each movement needed a pattern recognition method. The method used in designing this application is Hidden Markov Models. In designing this application using a Leap Motion camera that functions as a sensor to capture the movement of the skeleton in the hand. The sign language movement that is translated is SIBI sign language consisting of 5 words namely